2009
DOI: 10.1016/j.virol.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus HBx protein localized to the nucleus restores HBx-deficient virus replication in HepG2 cells and in vivo in hydrodynamically-injected mice

Abstract: Identifying the requirements for the regulatory HBx protein in hepatitis B virus (HBV) replication is an important goal. A plasmid-based HBV replication assay was used to evaluate whether HBx subcellular localization influences its ability to promote virus replication, as measured by real time PCR quantitation of viral capsid-associated DNA. HBx targeted to the nucleus by a nuclear localization signal (NLS-HBx) was able to restore HBx-deficient HBV replication, while HBx containing a nuclear export signal (NES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
56
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 56 publications
(97 reference statements)
12
56
0
Order By: Relevance
“…Although our observations imply that HBx exerts its role in potentiating HBV replication by acting directly on the cccDNA, we cannot exclude that Ca ϩϩ mobilization and src activation (13,15) might also play a role. Importantly, it has been recently reported that HBx protein localized to the nucleus restores HBx-deficient virus replication in HepG2 cells and in vivo in hydrodynamically injected mice (39), thus supporting the importance of HBx interaction with the cccDNA in the nucleus. Altogether our results indicate that HBx influences the epigenetic control of nuclear HBV cccDNA function by modulating the recruitment of chromatinmodifying enzymes onto the viral minichromosome.…”
Section: Discussionmentioning
confidence: 82%
“…Although our observations imply that HBx exerts its role in potentiating HBV replication by acting directly on the cccDNA, we cannot exclude that Ca ϩϩ mobilization and src activation (13,15) might also play a role. Importantly, it has been recently reported that HBx protein localized to the nucleus restores HBx-deficient virus replication in HepG2 cells and in vivo in hydrodynamically injected mice (39), thus supporting the importance of HBx interaction with the cccDNA in the nucleus. Altogether our results indicate that HBx influences the epigenetic control of nuclear HBV cccDNA function by modulating the recruitment of chromatinmodifying enzymes onto the viral minichromosome.…”
Section: Discussionmentioning
confidence: 82%
“…Results have shown that the absence of HBx can induce a 65% reduction in HBV replication (6), and trans-complementation of HBx for the HBx-deficient plasmid can restore replication to wild-type levels (6)(7)(8). Another advanced study performed with the hydrodynamic injection of an HBx-deficient plasmid into mice showed the same results in vivo (6,9,10). These results demonstrated that HBx has an important role in modulating HBV replication.…”
Section: Introductionmentioning
confidence: 71%
“…Human embryonic kidney 293T and liver HepG2 cells were maintained in Eagle's minimum essential medium (EMEM) with 10% fetal bovine serum (FBS), as previously described (23). Plasmid DNA encoding IPS-1 containing hemagglutinin (HA) and FLAG epitopes was obtained from Zhijian Chen (28).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid DNA encoding IPS-1 containing hemagglutinin (HA) and FLAG epitopes was obtained from Zhijian Chen (28). Plasmid DNA encoding HBx (subtype adw2) was prepared by cloning into plasmid vector pSI (Promega) as previously described (23). pSI-X plasmids with an in-frame nuclear localization signal (pSI-NLS-X) or a nuclear export signal (pSI-NES-X) were previously described (23).…”
Section: Methodsmentioning
confidence: 99%